A FAUNA DE LAGARTOS EM TRÊS BREJOS DE ALTITUDE DE PERNAMBUCO, NORDESTE DO BRASIL - Abrantes, Stephenson Hallison F.; Abrantes, Marcela M. Ramos; Falcão, Ana Cecília G. Pereira (Revista Nordestina de Zoologia, 2011)
The importance of the northeastern upland forests (brejo de altitude) have been highlighted since 1980 in terms of history and biogeography, suggesting that they should represent remnants of a connection that would have existed between the Amazon and Altlantic Forests. Nevertheless, there is still a knowledge gap about lizards fauna, what shows that it needs more research. The lizards fauna of three upland forests were studied from the state of Pernambuco and compared to other 20 locations from different brazilian’s ecosystems using the Sorensen’s similarity coefficient. A total of 29 lizards was found to those altitude wetlands. Faunistic groups obtained in this study show that the composition of all locations seems to obey to a connection with the type of vegetation of the locations where they occur. The results indicate that the Pernambuco’s upland forests constitute an important area for conservation, since they present unique evolutionary history within one of the most threatened ecosystems of the world.